Kajian Kesuburan Lahan untuk Evaluasi Lahan Kaitannya untuk Mitigasi Bencana Kekeringan di Kabupaten Nganjuk - Dyah Nursita Utami; Hasmana Soewandita (Agency for the Assessment and Application of Technology / Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Nganjuk Regency is a potential agricultural granary. Results fields and plantations is one supporting the needs of farms and plantations in East Java in particular and Java in general. Agricultural production in Nganjuk Regency often experiences fluctuating phases, one of which is due to drought. Assessment of soil fertility for land suitability evaluation into one of the efforts in mitigating drought in Nganjuk. This soil fertility assessment is carried out by taking soil samples based on the unit of land maps (SPL). Unit of land maps obtained from the overlay of base maps such as soil type maps, land use maps, topographic maps and administrative maps Nganjuk. The results of the laboratory analysis of soil samples subsequently analyzed and interpreted to obtain: 1) soil fertility status in Nganjuk; 2) determine suitability class; 3) determine the characteristics of an influential land for the development of food crops and plantations; 4) obtain recommendations or technologies efforts in tackling drought in Nganjuk.